TINJAUAN KONSTITUSIONAL PROSEDUR PEMBERHENTIAN PRESIDEN DAN/ATAU WAKIL PRESIDEN SEBELUM DAN SESUDAH PERUBAHAN UNDANG-UNDANG DASAR REPUBLIK INDONESIA TAHUN 1945 - Affandi, Muhammad; Affandi, Muhammad; abra, emy hajar (PETITA, 2019)
First, the procedure of dismissing the President and / or Vice President of the Republic of Indonesia Before Amendment of the 1945 Constitution. Before the amendment of the 1945 Constitution, the procedure for dismissal of the President and / or Vice President is preceded by the opinion (allegation) made by the House of Representative and / or Vice President submitted to the MPR. The MPR will hold a court to decide the opinion which has been submitted by the House of Representative. At this time the procedure for dismissal of the President and / or Vice President is not included in the 1945 Constitution. Second, the procedure for dismissing the President and/or Vice President of the Republic of Indonesia after the Amendment of the 1945 Constitution. After the amendment of the 1945 Constitution, the procedure for dismissal of the President and/or Vice President shall be initiated by the opinion of the House of Representative. The opinion was submitted to the Constitutional Court to examine, prosecute and decide by the opinion of the House of Representative. If the Constitutional Court confirms the opinion of the House of Representative then the case file will be returned to House of Representative to proceed to the MPR. MPR will conduct a hearing to decide the opinion submitted by the House of Representative. At this time the procedure for dismissal of the President and/or Vice President is clearly stated in Article 7A and 7B of the 1945 Constitution.Not only that, in this study the author also conducted a comparison of dismissal procedure of President and/or Vice President between Republic of Indonesia, United States and Filipina. In general, the dismissal of the President and/or Vice President between the United States and the Philippines is the same, which is preceded by the House of Representative applying the indictment to the Senate. Then the Senate tried the case by chaired by the Chief of Supreme Court in each country. At the court also directly decided whether the President and/or Vice President can be dismissed or not from his position. Judging from the procedure, the dismissal of the President and/or Vice President of the United States and Philippines adopts an impeachment model.